Genetic Analysis of Maize (Zea mays L.) Hybrids Using Microsatellite Markers - Eminur Elçi; Tuğçe Hançer (Journal of Agricultural Sciences)
Genetic purity is one of the most important quality criteria required for successful hybrid seed production. In this study, molecular markers were used for assessing the genetic purity and diversity of three commercially important maize F1hybrids (Pasha, Frida and PG1661) and their parental inbred lines. Fifty Simple Sequence Repeats (SSRs) markers were used to analyze samples, also the efficiency of the markers were compared. Twenty three primer pairs among the fifty markers were able to detect polymorphism between the different types of hybrids with an average of 0.69 polymorphism information content (PIC) value. Genetic purity analyses revealed more than 98% homogeneity in the hybrid seeds. The hybrids were grouped into three main clusters. It can be concluded that, molecular markers are efficient to study the genetic purity and diversity in maize hybrids and microsatellites are more accurate marker-type because of their co-dominancy